PP.23.09: ASSOCIATIONS OF SERUM 25-HYDROXYVITAMIN D AND PARATHYROID HORMONE WITH AMBULATORY HYPERTENSION AND THEIR INTERACTIONS WITH SERUM ALDOSTERONE AND SALT INTAKE. (June 2015) - Li, L.H.; Cheng, Y.B.; Zhang, L.; Wei, F.F.; Kang, Y.Y.; Wang, S.; Huang, Q.F.; Sheng, C.S.; Wang, J.G.; Li, Y.
Abstract : Objective: Recent studies suggest that vitamin D and parathyroid hormone (PTH) participate in blood pressure (BP) regulation, possibly via their interactions with the RAS system and salt homeostasis. With the use of the state-of-art ambulatory BP monitoring, we investigated associations of serum 25-hydroxyvitmainD (25[OH]D) and PTH with hypertension and their interactions with serum aldosterone and salt intake. Design and method: We recruited consecutive patients referred for ABPM to our clinic, if they had never taken (∼90%) or had discontinued antihypertensive medication for at least 2 weeks (∼10%). We programed SpaceLabs 90217 monitors to obtain 24-h ambulatory BPs. Daytime and nighttime were defined as time intervals from 8:00 to 18:00 and from 23:00 to 5:00, respectively. Serum 25(OH)D and PTH were measured by electrochemiluminescence immunoassay and aldosterone by radioimmunoassay, and these biomarkers were log-transformed for statistical analyses. Linear and logistic regression analyses were performed to investigate the associations of interest. Results: The 1117 participants (50.4% women) included 699 patients with ambulatory hypertension, 845 with 25(OH)D deficiency (<50 nmol/L), and 490 patients with PTH excess (>65 pg/mL). In unadjusted analyses, 25(OH)D was negatively associated with daytime diastolic BP (P = 0.018), while PTH was positively associated with 24-h and nighttime BPs (P < 0.030), and aldosterone with all ambulatory BPs (P < 0.034). After multivariate adjustment, all above associations remained significant except for the associations of 24-h and nighttime diastolic BP with aldosterone (P = 0.07). In multivariate analyses, both 25(OH)D deficiency (OR [95%CI];1.46 [1.07–2.00], P = 0.019) and PTH excess (1.32 [1.01–1.74], P = 0.043) were associated with 24-h ambulatory hypertension. In addition, there were significant (P < 0.02) interactions between 25(OH)D and 24-h urinary sodium excretion in relation to 24-h and daytime diastolic BP, and between serum PTH, aldosterone and 24-h urinary sodium excretion in relation to nighttime BP. In subjects with 24-h urinary sodium excretion above, but not below, the median (153 mmol), PTH excess was associated with a higher nighttime systolic (+4.2 mm Hg, P = 0.0004) and diastolic BP (+3.1 mm Hg, P = 0.0002). Conclusions: Both vitaminD deficiency and PTH excess are associated with ambulatory hypertension. These associations might be modulated by its interactions with salt intake and aldosterone secretion.